Dose response to supplemental fat by finishing steers - Gramlich, S.M.; Brandt, Robert T., Jr.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A trial with 100 head of crossbred steers (avg wt 879 lb) was conducted to determine the effects of tallow (none, 2, 4, 6, 8% of ration dry matter) on the performance and carcass characteristics of finishing cattle fed a corn-based diet. Protein levels were maintained at a constant ratio to the calculated metabolizable energy concentration of the diets. Initially, feed intake decreased as tallow increased; however, similar intakes were obtained after 11 days. Dry matter intakes throughout the finishing period were reduced 5.2, 6.9 and 7.7%, respectively, for the 4, 6 and 8% tallow diets. Average daily gain was similar for the control, 2, and 4% levels and declined 4.9 and 13.3% for the 6 and 8% tallow diets, respectively. Feed efficiency had a quadratic relationship with added fat and was best at 4% fat. There were no significant differences in carcass traits among treatments. Therefore, for steers finished on corn-based diets, 4% tallow appeared to be optimum, considering performance, efficiency, and carcass quality.
Keywords: Beef; Tallow; Finishing; Performance; Carcass traits